Strategic Approaches to Enhancing Adolescents’ Religious Character through Faith-Based Activities - Ahmad Sulaiman; Nelly Marhayati; Mindani Mindani (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2026)
This study aims to analyze strategies for strengthening religious character among adolescents in Tanjung Tebat Village and to identify supporting and inhibiting factors. The research problem centers on the lack of consistency in religious character development among rural youth outside formal schooling. A descriptive qualitative approach was applied using field research. Data were collected through observation, interviews, and documentation. Data validity was ensured through triangulation by comparing results across sources. Analysis involved data reduction, display, and conclusion drawing. The findings reveal that religious values are developed through community-based activities such as mukhadarah (religious speech training) and congregational Dhuhr prayers. Additional focus is given to Qur’an reading skills and adherence to Islamic dress codes, especially among female adolescents. The character-building process includes stages of introduction, internalization, habituation, and implementation, monitored through behavioral discipline and social reinforcement. Supporting factors include internal motivation, family involvement, and the commitment of community religious facilitators. Inhibiting factors involve limited male role models and inadequate religious facilities. These results highlight the importance of non-formal, community-driven religious education in shaping adolescent character in rural areas.